2014
DOI: 10.1016/j.poly.2014.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Cyclometalated rhodium and iridium complexes with imidazole containing Schiff bases: Synthesis, structure and cellular imaging

Abstract: Cyclometalated rhodium(III) and iridium(III) complexes (1–4) of two Schiff base ligands L1 and L2 with the general formula [M(ppy)2(Ln)]Cl {M = Rh, Ir; ppy = 2-phenylpyridine; n = 1, 2; L = Schiff base ligand} have been synthesized. The new ligands and the complexes have been characterized with spectroscopic techniques. Electrochemistry of the complexes revealed anodic behavior, corresponding to an M(III) to M(IV) oxidation. The X-ray crystal structures of complexes 2 and 4 have also been determined to interpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 80 publications
3
24
0
Order By: Relevance
“…1 This ease of synthesis coupled with the ubiquitous nature of imidazole moieties in enzymes, proteins and pharmaceuticals render it a favourable choice in biological studies. 1,2 Additionally, Schiff base ligands are able to coordinate and stabilise metals in a wide range of oxidation states. [2][3][4][5][6][7][8] Metal complexes of imidazole-based Schiff base ligands have therefore found application in a wide variety of elds including medicinal and biological chemistry as well as catalysis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 This ease of synthesis coupled with the ubiquitous nature of imidazole moieties in enzymes, proteins and pharmaceuticals render it a favourable choice in biological studies. 1,2 Additionally, Schiff base ligands are able to coordinate and stabilise metals in a wide range of oxidation states. [2][3][4][5][6][7][8] Metal complexes of imidazole-based Schiff base ligands have therefore found application in a wide variety of elds including medicinal and biological chemistry as well as catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Additionally, Schiff base ligands are able to coordinate and stabilise metals in a wide range of oxidation states. [2][3][4][5][6][7][8] Metal complexes of imidazole-based Schiff base ligands have therefore found application in a wide variety of elds including medicinal and biological chemistry as well as catalysis. 1 In recent years, derivatives of the 1-methyl-imidazol-2-yl methylidine Schiff Base ligand have been co-ordinated to various metals for a wide variety of applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soft systems are large and highly polarisable, while hard systems are relatively small and much less polarisable. Mandal et al[75] reported the cyclometalated rhodium and iridium complexes with imidazole containing Schiff bases and the HOMO, LUMO values are 48.73 and 16.21 eV for iridium complexes and 49.02 and 16.78 eV, rhodium complexes with imidazoles.…”
mentioning
confidence: 99%
“…Guo and Velmathi developed a fluorescent turn‐on recognition of anions by the intermolecular hydrogen bond inhibited C=N isomerization mechanism. Although these Schiff‐base compounds are widely used because of their facile synthesis, remarkable versatility, strong coordination abilities and good solubility in common solvents, their short fluorescence wavelength, short lifetime and low quantum yield make them more complicated especially in live cell imaging where these chromophores result from photobleaching and loss of signal …”
Section: Introductionmentioning
confidence: 99%